Answer:
BCG =65
Step-by-step explanation:
DCG + GCB = DCB
We know BCG = 31x+3 and GCD = 12x+2 and BCD = 91
Substituting these in
12x+2 + 31x+3 = 91
Combine like terms
43x +5 = 91
Subtract 5 from each side
43x+5-5 = 91-5
43x = 86
Divide by 43
43x/43= 86/43
x=2
BCG = 31x+3
=31(2)+3
=62+3
=65
Answer:
b
Step-by-step explanation:
Answer:
12 of them
Step-by-step explanation:
2:4
4:8
6:12
basic stuff
1.remove parentheses by multiplying factors.
2.use exponent rules to remove parentheses in terms with exponents.
3.combine like terms by adding coefficients.
4.combine the constants
So first solve for x and y
add the 2 equations together
2x+x+y-y=-8-4
3x=-12
divide by 3
x=-4
subsitute
-4-y=-4
addd 4 to both sdies
-y=0
the solution is (x,y) (-4,0) or D